(untitled) (Journal of the Bangladesh Agricultural University, 2013)
An experiment was conducted at the Agronomy Field Laboratory, Bangladesh Agricultural University, Mymensingh during the period from April to August 2011 to find out the effect of spacing and number of seedlings hill-1 on the performance of Aus rice cv. NERICA 1. Four spacing viz. 25 cm × l5 cm, 20 cm × l5 cm. 20 cm × 10 cm and 15 cm × 10 cm and four number of seedlings hill-1 viz. 2, 3, 4 and 5 were included in the experiment. The experiment was laid out in a randomized complete block design with three replications. The highest number of total tillers m-2, number of effective tillers m-2, number of grains panicle-1, grain yield, straw yield, biological yield and harvest index were obtained from 20 cm × 10 cm spacing. Plant height and 1000- grain weight were not significantly affected by spacing. Number of seedlings hill-1 exerts a significant effect on plant height. The highest value of total tillers m-2, number of effective tillers m-2, total grains panicle-1, grain yield, straw yield, biological yield and harvest index were obtained from five seedlings hill-1. The interaction between spacing and number of seedlings hill-1 significantly influenced yield and plant characters. The highest number of effective tillers m-2, grains panicle-1, grain yield, straw yield and biological yield were recorded from the interaction between 20 cm × 10 cm and five seedlings hill-1. DOI: http://dx.doi.org/10.3329/jbau.v10i2.14681 J. Bangladesh Agril. Univ. 10(2): 191-195, 2012